Beginning JBoss Seam From Novice to Professional - Faisal Nusairat, Joseph; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2007)
Reacting to the popularity of Java 2.0 Enterprise Edition™ alternatives such as Ruby on Rails and the enterprise Spring Framework, Red Hat JBoss®, Inc. developed JBoss® Seam, a new open-source lightweight Java™ EE 5-based contextual application development framework. Beginning JBoss® Seam: From Novice to Professional gets you started as the first book on this popular framework.
What Is JBoss Seam? -- Web Applications -- JSF Fundamentals -- EJB3 Fundamentals -- to Seam -- Seam Contexts -- Business Process in Seam -- Advanced Topics -- Advanced Configurations -- Seam Tools.
Keywords: Java (Computer program language).; Software engineering; Java; Software Engineering/Programming and Operating Systems